Modernization of the USSR Pipe Industry in the 1950s: Based on Archival Materials of Policy-Making Bodies - Zapariy, Vladimir V.; Zaitseva, Ekaterina V. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Istoriâ Rossii (Print), 2025)
The authors, through their article, examine the activities of the policymaking bodies in organizing the modernization of the pipe industry of the Soviet Union in the 1950s, a period when a need to rapidly develop oil and gas pipeline transport arose and there was a switch to larger diameter and higherpressure pipes than before. Due to limited internal resources, the Soviet industry before that time could not produce the required range of pipes. The authors analyzed the documents of the highest governing bodies of the USSR from the funds of the Russian State Archive of Modern History, which made it possible to determine the strategy for the modernization of the pipe industry in the USSR in the 1950s, and to assess the level of pipe production in the country, and to reveal its discrepancy with the needs of the developing industry. By analyzing investment projects of the USSR into the pipe industry, the authors examine the scale of construction of new production facilities and the practice of importing pipes during the period under review. The authors come to the conclusion that in order to solve the problem set by the country’s leadership, the policymaking bodies took a number of important measures. In particular, the production plans of pipe plants were revised in order to increase the output of products of the required sizes and characteristics, and a program for the reconstruction and modernization of outdated production facilities was launched, a program which included the introduction of new technologies. Furthermore, negotiations by the state were conducted with foreign suppliers on the purchase of the necessary volumes of pipes. This comprehensive approach made it possible to ensure the development of the oil and gas pipeline system of the USSR through the 1950s.